Zakat dan Keadilan Ekonomi Perspektif Islam, Kapitalisme, dan Sosialisme - Ahmad Jalili; Hasbi Umar; Hermanto Harun (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2022)
Justice was a benchmark in an economic system. With the implementation of the current economic system, such as the capitalist and socialist economic systems, there were often social injustices in the economy. The measure was a large number of social inequalities between communities that spike in poverty or unemployment in the country. Therefore we need an economic system solution for the welfare of the people, namely an Islamic economic system. One of the solutions presented in the Islamic economic system was zakat. Zakat was one of the commands of the Islamic religion which was considered worship or good deeds that can influence others. Islam places great importance on justice in all matters. Justice must be served to everyone. Islam also regulates justice in the economic field. This study reveals justice that was highly emphasized that Islam was justice in the distribution of assets, one of which was zakat.